2006
DOI: 10.1177/0002716205285889
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Katrina and the Flooding of New Orleans: Emergent Issues in Sheltering and Temporary Housing

Abstract: Hurricane Katrina created an unprecedented need for sheltering and temporary housing across a four-state area along the Gulf Coast. This article reviews the disaster literature with respect to sheltering and temporary housing and contrasts how these needs actually developed with respect to both the preimpact and postimpact evacuation situations. The article also investigates the ways that intergovernmental planning failed to anticipate the need for shelter/housing solutions or to implement effective measures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 4 publications
1
46
0
Order By: Relevance
“…Research conducted in communities that received evacuees from Hurricane Katrina showed that the magnitude of the people involved overwhelmed state and local capabilities to assist evacuees and also began to put a strain on community services. 11,15 Feelings of stress were widespread in the four regions, and additional eating, smoking, and drinking were found. Public health systems should include increased education about positive countermeasures to stress following natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in communities that received evacuees from Hurricane Katrina showed that the magnitude of the people involved overwhelmed state and local capabilities to assist evacuees and also began to put a strain on community services. 11,15 Feelings of stress were widespread in the four regions, and additional eating, smoking, and drinking were found. Public health systems should include increased education about positive countermeasures to stress following natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Of unprecedented magnitude, this disaster revealed problems in emergency shelter and temporary housing at pre-and post-disaster stages. For example, adequate places of refuge must be identified in advance, but the potential for them to become dangerous sites themselves in need of evacuation if a disaster worsens, or impossible to staff, provision and manage especially if evacuee numbers reach the thousands and not just hundreds, was also then brought home (Nigg et al, 2006). Full recovery does not necessarily or quickly follow a response.…”
Section: Disasters and Housingmentioning
confidence: 99%
“…A house is a space for people to live in, providing conditions for family life, comfort, protection, and privacy. Disaster relief efforts should prioritize the need for housing, because the loss of a house involves more than physical deprivation; it represents the loss of dignity, identity, and privacy [3,4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the provision of shelters is widely accepted as a necessary component of response and recovery following disasters such as earthquake, hurricanes, tsunamis, and floods, it is not yet clear which type of shelter is best as in certain cases shelter implementation has been hindered by inappropriate climate, cultural differences, poorly located settings, camp-related social issues, expenses, overcrowding, poor services, and delays [6, [11][12][13]. In addition, the design of shelters may potentially provide an unacceptable standard of living.…”
Section: Introductionmentioning
confidence: 99%